Spain : Landmarks in Economic Development, 1939-92 - Spitaller, Erich; Galy, Michel (Washington, D.C. : International Monetary Fund, 1992)
Recent success of the Spanish economy is frequently attributed to the benefits from economic integration into the European Community, which Spain joined in 1986. By contrast, this paper takes the view that, to a large extent, the origins of success may be traced back to earlier years and that the benefits from EC membership are best seen as reinforcing favorable trends already in effect. Exploring Spain's economic development from a longer-run perspective, with emphasis on interaction of events at home and abroad, the paper assesses the financial and structural policy record for its contributions to success. Most significant are the 'orthodox' stabilization and reform program under the auspices of the Fund in 1959, the 'heterodox' adjustment program pursued on transition to democracy in 1977 and the differences in the response of policy to the oil crises of the early and late 1970s. On the whole, the approach to financial stabilization was radical, and that to structural reform gradual. The paper concludes that by mid-1980 Spain had largely accomplished the transition to a modern economy and prospects were favorable for sustainable expansion over the medium term. The mutually reinforcing effects of those circumstances and the subsequent process of integration into the EC spurred the further progress of Spain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet